11 days in August: A Chronicle of the Aquino Assasination (Manila, Philippines Communication Foundation for Asia)
A documentary chronicle presenting the events surrounding the assassination of Philippine opposition leader Benigno "Ninoy" Aquino Jr. in August 1983 and the political and social developments that followed in the Philippines.
Documentary film about the assassination of Benigno Aquino Jr. and the events that followed.
PG-13
Keywords: Political assassinations; Philippines - history